Peningkatan Kompetensi Guru Fisika Tingkat SMA dalam Eksperimen Fisika Menggunakan Software Video Tracker - Natalisanto, Adrianus Inu; Hamdani, Dadan; Muliyono, Suhadi; Intifadhah, Sahara Hamas; Munir, Rahmawati; Salamah, Alifah Balqis (ANDIL Mulawarman Journal of Community Engagement, 2025)
This community service activity aims to enhance the competence of high school physics teachers in East Kalimantan in using the Video Tracker software to support physics experiments. A total of 20 physics teachers participated with very high enthusiasm. The methods used in this activity included the Lecture Method, where participants were introduced to the basic theories and concepts of motion that can be analyzed using Video Tracker, the Demonstration Method, where the direct application of the software was shown to the participants, and the Assistance Method, where participants were guided step-by-step in conducting physics experiment simulations using Video Tracker. The results showed that teachers improved their skills in analyzing motion data using technology, which is expected to enrich the teaching process of physics in schools.